2008
DOI: 10.3354/meps07823
|View full text |Cite
|
Sign up to set email alerts
|

Fishes in high-CO2, acidified oceans

Abstract: Research interest in CO 2 -driven ocean acidification has been centered on certain groups of calcifying marine organisms, but knowledge on the possible impacts of ocean acidification on fish is limited. Our survey of the existing literature on the effects of increased pCO 2 on fish (total of 116 papers) revealed that few studies were conducted under pCO 2 conditions relevant to the future scenarios of ocean acidification. Information is nearly absent on reproduction, early development, and behaviour of marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
196
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(212 citation statements)
references
References 69 publications
4
196
3
2
Order By: Relevance
“…Sperm motility of the flounder, Limanda yokohamae, is arrested by mild increases in pCO 2 (Inaba et al 2003), but similar effects were not observed in 10 other species from a range of families (Inaba et al 2003) or in the Baltic cod, Gadus morhua (Frommel et al 2010). Sensitivity of fish eggs to elevated CO 2 varies markedly between species, but species tested to date typically have 24-h LC50 (lethal concentration resulting in 50% mortality) values well above 10 000 ppm CO 2 (Ishimatsu et al 2008). Furthermore, Munday et al (2009a) did not detect any effect of exposure to 1000 ppm CO 2 on the embryonic duration or survival of clownfish (Amphiprion percula) eggs.…”
Section: Ocean Acidification and Reproductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sperm motility of the flounder, Limanda yokohamae, is arrested by mild increases in pCO 2 (Inaba et al 2003), but similar effects were not observed in 10 other species from a range of families (Inaba et al 2003) or in the Baltic cod, Gadus morhua (Frommel et al 2010). Sensitivity of fish eggs to elevated CO 2 varies markedly between species, but species tested to date typically have 24-h LC50 (lethal concentration resulting in 50% mortality) values well above 10 000 ppm CO 2 (Ishimatsu et al 2008). Furthermore, Munday et al (2009a) did not detect any effect of exposure to 1000 ppm CO 2 on the embryonic duration or survival of clownfish (Amphiprion percula) eggs.…”
Section: Ocean Acidification and Reproductionmentioning
confidence: 99%
“…In general, fishes appear to be more tolerant to increases in ambient CO 2 than many invertebrates (Ishimatsu et al 2008;Widdicombe and Spicer 2008), possibly because of their welldeveloped mechanisms for acid-base regulation (Pörtner et al 2004;Melzner et al 2009). However, very little is known about the effects that chronic exposure to levels of pCO 2 predicted to occur over the next 50-100 years (up to ,1000 ppm CO 2 ) might have on fish reproduction.…”
Section: Ocean Acidification and Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, calcifying phytoplankton and invertebrates such as corals and mollusks have received the most attention due to the potential impact of acidification on carbonate shell integrity and formation [3,4]. By contrast, fish were initially believed to be safe from the effects of OA, as early studies demonstrated a lack of mortality under extremely high CO 2 levels (greater than 10 000 matm) [5]. However, an increasing body of evidence suggests that OA-relevant CO 2 /pH levels induce various sublethal effects in fish, including otolith over-growth [6,7], a shift in behavioural lateralization [8,9], alterations in olfaction that affect detection of cues from substrates, parents [10], prey [11] and predators [8,12,13], and impaired learning [9,14].…”
Section: Introductionmentioning
confidence: 99%